Neuromuscular ankle joint stabilisation after 4-weeks WBV training - Melnyk, M.; Schloz, C.; Schmitt, S.; Gollhofer, A. (International Journal of Sports Medicine, 2009)
Whole body vibration (WBV) training is increasingly implemented in prevention programs as well as in rehabilitation protocols but evidence for beneficial effects of WBV training over several weeks on ankle joint stabilisation is lacking. The purpose of the study was to investigate the effects of 4-weeks WBV training on reflex activity of the long peroneal and tibialis anterior muscles and on the duration of ankle inversion movement in response to an unexpected combined 24° inversion 15° plantar flexion ankle joint motion. Twenty-six healthy subjects were divided into an intervention group (n=16) and a control group (n=10). The intervention group trained thrice weekly for 3 min on a unidirectional oscillating vibration platform (30 Hz, 4 mm amplitude). Pre and post intervention reflex activity were measured and the duration of ankle joint movement was calculated by vertical ground reaction forces. After four weeks of WBV training no significant changes were found in latencies and reflex activity in both muscles in response to ankle sprain simulation. Similar results were observed for the time of ankle inversion motion. Based on the present results, it is unlikely that 4-weeks WBV training has beneficial effects on ankle joint stability in the case of an ankle inversion motion.